(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2025)
In forensic science, bite mark analysis is important because it produces crucial evidence for criminal investigations. This review will discuss the anatomy and characteristics of bite marks, trace the historical development of such within the discipline, and trace such historical development. The report addresses how various methods are employed in analyzing the marks, focusing on advances in imaging methods and comparative analysis techniques. Further, it discusses the problems that forensic experts face today and repercussions of the new technology. To enhance more preciseness and reliability, the final section of the report focuses on future directions for bite mark forensic science research and practice. It highlights the urgency for standardized processes and inter-professional collaboration.